IgG4 related disease in a seven year old girl with multiple organ involvement: A rare presentation - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Autoimmune pancreatitis has been described as a pancreatic manifestation of immunoglobulin G4-related disease, which is characterized by typical histopathologic, radiologic, and clinical features. Immunoglobulin G4-related disease is usually accompanied by elevated serum immunoglobulin G4 level, and can involve multiple organ/systems. Immunoglobulin G4-related disease has rarely been reported in pediatric population. There are few reports of inflammatory bowel disease in association with immunoglobulin G4-related disease. We describe a 7-year-old girl who presented with pancreatitis and concurrent sclerosing cholangitis, and developed bloody diarrhea during follow-up. An endoscopic examination revealed inflammatory bowel disease, and later lacrimal gland involvement was also recognized. She was diagnosed as having immunoglobulin G4-related disease, and her clinical signs and symptoms improved dramatically after steroid treatment. Hence, awareness of the clinical picture is important and early diagnosis can prevent fibrosis and organ damage.
Keywords: Autoimmune pancreatitis; child; immunoglobulin G4-related disease; AUTOIMMUNE PANCREATITIS; DIAGNOSIS